1995
DOI: 10.3133/ofr95136
|View full text |Cite
|
Sign up to set email alerts
|

Water-quality assessment of the Albemarle-Pamlico drainage basin, North Carolina and Virginia environmental setting and water-quality issues

Abstract: This information will help support the development and evaluation of management, regulatory, and monitoring decisions by other Federal, State, and local agencies to protect, use, and enhance water resources. The goals of the NAWQA Program are being achieved through ongoing and proposed investigations of 60 of the Nation's most important river basins and aquifer systems, which are referred to as study units. These study units are distributed throughout the Nation and cover a diversity of hydrogeologic settings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 9 publications
0
45
0
Order By: Relevance
“…Average annual precipitation ranges from 36 inches in the western part of the Albemarle-Pamlico Drainage Basin to 52 inches in the eastern part of the basin (McMahon and Lloyd, 1995). This water leaves the basin by way of streams and ground water.…”
Section: Environmental Setting and Hydrologic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average annual precipitation ranges from 36 inches in the western part of the Albemarle-Pamlico Drainage Basin to 52 inches in the eastern part of the basin (McMahon and Lloyd, 1995). This water leaves the basin by way of streams and ground water.…”
Section: Environmental Setting and Hydrologic Conditionsmentioning
confidence: 99%
“…Average water use during 1990 in the Albemarle-Pamlico Drainage Basin was about 2,800 million gallons per day (Mgal/d) (McMahon and Lloyd, 1995). Most of this water is from surface water (90 percent) with the remaining 10 percent supplied from ground water ( fig.…”
Section: Environmental Setting and Hydrologic Conditionsmentioning
confidence: 99%
“…1). Soils vary from fine to moderately fine textures in the coastal plain and piedmont areas (McMahon and Lloyd, 1995). The climate is warm and humid with rainfall evenly distributed throughout the year.…”
Section: Raleighmentioning
confidence: 99%
“…The estimated input from wastewater discharge was 1,500 lb/yr for nitrogen (table 6). The error in this estimate is unknown, because it is based on a set of data outside the study area and because the variability around this relation is not shown in McMahon and Lloyd (1995). Estimated inputs from wastewater discharge for total phosphorus were not available.…”
Section: Point-source Contributionsmentioning
confidence: 99%